Quality of worklife: a human values approach - Datta, Tanmoy (1999)
In a deeper sense, quality of worklife (QWL) refers to the quality of life (QL) of individuals in their working organizations - commercial, educational, cultural, religious, philanthropic or whatever they are. Modern society is organizational society. Individuals spend much of their lives in organizations. Hence, the importance of QWL is unquestionable. It has an ideological core comprising the perceptual gap across individuals about the real connotation of QL as well as QWL. In addition to this ideological problem, the study of QWL presents serious methodological problems too. A positivist attitude is always sceptical about the deeper meaning of life, may be out of honest lack of knowledge, or may be with some ulterior motives. The present paper therefore is an attempt to touch upon three aspects of QWL: (a) QWL from a human values approach; (b) some view points for subjective observation of QWL; and (c) some ameliorative measures towards improving QWL. - Reproduced
Keywords: Quality of working life